the implementation of supervisory activities by the head of the madrasa in improving the discipline of teachers and students at MIN 9 Pidie, Pidie District: A literature study. - herman putra (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study investigates the pivotal role of supervisory activities conducted by the head of the madrasa in enhancing both teacher and student discipline at MIN 9 Pidie, located in Pidie District. The focus is on understanding how effective leadership can foster a structured and respectful learning environment that encourages academic success and personal development. Utilizing a comprehensive literature review, the research examines various theoretical frameworks related to educational leadership, supervision, and school discipline. It highlights the critical responsibilities of madrasa heads, which include establishing clear expectations, implementing consistent monitoring practices, and actively engaging with teachers and students to cultivate a positive school culture. The study also explores the significance of communication and collaboration in the supervisory process, emphasizing the need for an inclusive approach that maximizes stakeholder participation. Through an analysis of relevant studies and best practices, the research identifies specific strategies employed by the head of MIN 9 Pidie to reinforce discipline. These strategies encompass regular monitoring of classroom activities, providing constructive feedback to teachers, facilitating professional development opportunities, and fostering student engagement through incentive programs designed to reward positive behavior. Moreover, the findings underscore the correlation between systematic supervision and improved outcomes in the educational milieu. Effective supervisory practices not only enhance teacher accountability and performance but also promote student responsibility and self-discipline. This synergy ultimately contributes to a more effective learning environment, increased academic performance, and the overall development of students as responsible individuals.